Bone‐marrow‐derived mesenchymal stem cells inhibit gastric aspiration lung injury and inflammation in rats. Issue 9 (7th April 2016) - Zhou, Jing; Jiang, Liyan; Long, Xuan; Fu, Cuiping; Wang, Xiangdong; Wu, Xiaodan; Liu, Zilong; Zhu, Fen; Shi, Jindong; Li, Shanqun
Abstract: Gastric aspiration lung injury is one of the most common clinical events. This study investigated the effects of bone‐marrow‐derived mesenchymal stem cells (BMSCs) on combined acid plus small non‐acidified particle (CASP)‐induced aspiration lung injury. Enhanced green fluorescent protein (EGFP + ) or EGFP − BMSCs or 15d‐PGJ2 were injected via the tail vein into rats immediately after CASP‐induced aspiration lung injury. Pathological changes in lung tissues, blood gas analysis, the wet/dry weight ratio (W/D) of the lung, levels of total proteins and number of total cells and neutrophils in bronchoalveolar lavage fluid (BALF) were determined. The cytokine levels were measured using ELISA. Protein expression was determined by Western blot. Bone‐marrow‐derived mesenchymal stem cells treatment significantly reduced alveolar oedema, exudation and lung inflammation; increased the arterial partial pressure of oxygen; and decreased the W/D of the lung, the levels of total proteins and the number of total cells and neutrophils in BALF in the rats with CASP‐induced lung injury. Bone‐marrow‐derived mesenchymal stem cells treatment decreased the levels of tumour necrosis factor‐α and Cytokine‐induced neutrophil chemoattractant (CINC)‐1 and the expression of p‐p65 and increased the levels of interleukin‐10 and 15d‐PGJ2 and the expression of peroxisome proliferator‐activated receptor (PPAR)‐γ in the lung tissue in CASP‐induced rats. Tumour necrosis factor‐α stimulated BMSCs to secrete 15d‐PGJ2 . A tracking experiment showed that EGFP + BMSCs were able to migrate to local lung tissues. Treatment with 15d‐PGJ2 also significantly inhibited CASP‐induced lung inflammation and the production of pro‐inflammatory cytokines. Our results show that BMSCs can protect lung tissues from gastric aspiration injury and inhibit lung inflammation in rats. A beneficial effect might be achieved through BMSC‐derived 15d‐PGJ2 activation of the PPAR‐γ receptor, reducing the production of proinflammatory cytokines.